A Thematic Approach to Realize Multidisciplinary Community Service-Learning Education to Address Complex Societal Problems: A-Win-Win-Win Situation? - Tijsma, Geertje; Urias, Eduardo; Zweekhorst, Marjolein (Frontiers in Education, 2021)
Universities are under increasing pressure to become more and better involved in society as part of their third mission, to which Community Service learning (CSL) can contribute. To date, most CSL projects are mono-disciplinary, single courses, often of a short-term nature. In order to address the increasingly complex problems facing society, there is a need to adopt multi- and interdisciplinary CSL approaches that allow for a range of perspectives. The article describes and analyzes how a thematic CSL approach was initiated at the VU Amsterdam starting from the needs of a local community. Once loneliness was identified as an important and relevant issue, the approach evolved in order to include multiple courses and internships from different programs offered by two faculties and various stakeholders and community organizations. Taking an action–research approach, the CSL team evaluated the process of its development, outcomes and contributions, as well as possible benefits and considerations. In addition to more tangible outcomes arising from many student projects, the approach assists in building new community networks, supports project continuity, deepens knowledge, encourages new collaborations, reduces CSL-created workload and finally increases student development, motivation and sense of ownership. Overall, it can be concluded that the thematic approach can contribute to addressing complex problems as it allows for multidisciplinary collaborations while not imposing too great a burden on the established curriculum. This makes the thematic CSL approach a valuable stepping stone in advancing CSL in universities, and so contribute to fulfilling their third mission.